The Flow Around a Lorry Platoon Subject to a Crosswind—a Detached Eddy Simulation - He, M.; Huo, S.; Hemida, H.; Soper, D.; Sterling, M.; Baker, C. (Frontiers in Future Transportation, 2022)
Technological developments in Connected and Autonomous Vehicles (AVs) have created opportunities to allow groups of vehicles to travel in close proximity, through methods known as platooning. There are potential benefits from platooning in terms of fuel consumption, through a reduction in aerodynamic drag for trailing vehicles in the platoon; however, it is still not understood whether these benefits remain when the platoon is subject to crosswind. For the first time, this study examines the flow structure and aerodynamic response of a platoon of eight closely spaced lorry type vehicles subjected to a crosswind with a 30o yaw angle. The numerical study is conducted using a Delayed Detached Eddy Simulation. It is observed that there is an increase in the overall drag when compared to a similar simulation with no crosswinds. Streamline illustrations indicate that a recirculation region is formed on the leeside of the lorries, which with the chosen vehicle spacing does not exhibit any interactions with the consecutive lorry, resulting in a diminished drag reduction. High pressure on the windward side of the lorries and a low pressure region on the top of the lorry boxes results in high lift, side force and rolling moment coefficients, but relatively minor pitching and yawing moments.